The Impact of Additive Manufacturing on the Acoustic Performance of Novel Porous Materials - Ciochon, Agnieszka Helena; Kennedy, John (My University, 2022)
Commonly used conventional acoustic porous materials suffer from a limited operational frequency range and great dependency of the sample thickness on their performance. For this reason, acoustic metamaterials have caught the eye of the scientific community with their ability to manipulate and absorb soundwaves despite their subwavelength dimensions. These novel acoustic materials are especially of interest for aerospace and automotive industries. Industrially relevant design tools are required to unlock the potential of these materials and the development of these tools requires benchmark problems. This work analyzes how the additive manufacturing process influences the acoustic performance of a periodic porous acoustic material. To answer this question, samples of a benchmark material were fabricated using selective laser melting with a 0.03 mm layer height. An optical microscope, a confocal microscope and computerized tomography scanner were used to examine manufactured specimens and provide insight into their surface topology. Numerical models of the structure were created. The computational results were compared with the experimental values. A combination of modelling strategies are investigated to incorporate features of the additive manufacture in the prediction of the acoustic behaviour. The observed mismatch between them can only partially be explained by the presence of the surface roughness. This study emphasizes the need to take into account more aspects of the additive manufacturing process when designing acoustic materials.
28th AIAA/CEAS Aeroacoustics Conference
PUBLISHED
I would like to upload the accepted version to TARA. According to the guideline: 'The above link and final published PDF are only for your personal use and is only accessible when logged in to your AIAA account. If you wish to post your article on your personal website or institutional repository, you may use the accepted version which is the version you submitted for acceptance. It is not the downloaded version from ARC. If you wish to share your published work with others, the link below provides free access for up to four users (shared among all authors) to your publication. You may send this link to colleagues that may be interested. If your paper is not published under an open access model, this free access link may NOT be used for commercial purposes or posted on openly accessible websites. Once four users activate access to your publication, there will be no more activation tokens available. Please send the following to share with others'. The published version is available here: https://arc.aiaa.org/doi/10.2514/6.2022-2903
Southampton, UK
Keywords: additive manufacturing; acoustic materials; surface roughness; SLM; Smart & Sustainable Planet; Additive Manufacturing; SLM; SURFACE ROUGHNESS; acoustic materials